Core-Competence Educational Policies Versus the Practical Realities of Rural Area-Based Language Teachers: Pathways to Better Policy Implementation - He Fang; He Xueyun (SAGE Open)
Foreign language acquisition significantly hinges on competencies that inform both teaching and learning. Despite the multiple language policies and frameworks like the CEFR (Common European Framework of Reference for Languages), there exists a gap in empirical research on the implementation of language policies by local education authorities in rural areas, where trainers’ needs and trainees’ circumstances are often different. Therefore, this study contributes to bridging this gap by analyzing how competency-based policies are implemented in rural areas via teacher training workshops organized by the local education board and schools. In total, 196 junior and senior high school teachers of English as a foreign language (EFL) in the rural areas surrounding Hengyang City in China were recruited to participate in the study. A mixed-method approach, consisting of analyzing quantitative and qualitative data gathered from a questionnaire, semi-structured interviews, a corpus comprising seven years of education policies, and workshop content, is analyzed in the study. The findings indicate that national language policies did not adequately align with teachers’ needs, and EFL teachers attended relatively few competency-based training workshops, which they perceived to be moderately useful in improving core competencies outlined in the policies. Furthermore, there were discrepancies in the needs of junior and senior high school TOE. The implications of the findings inform our reflection on adjusting the policy implementation structure at the rural level to customize the policies and reinforce competency-based training to reflect the realities of rural area-based parents, students, and TOE.